Do Certification Schemes Enhance Coffee Yields and Household Income? Lessons Learned Across Continents - Jena, Pradyot Ranjan; Grote, Ulrike (Frontiers in Sustainable Food Systems, 2022)
While the market for sustainably certified products grows, the debate on whether smallholder farmers benefit from this certification movement is far from over. We present empirical findings across three continents. Identical household surveys were conducted among 738 smallholder coffee farmers organized in primary cooperatives in Ethiopia, India and Nicaragua. The comparative analysis which is based on the propensity score matching approach shows that the impacts of Fairtrade certification on coffee yields and income vary across countries. In Ethiopia, the coffee farmers from Fairtrade certified cooperatives fare worse than their non-certified counterparts both in coffee yield and income. In the Indian case study, the Fairtrade cooperative members have yield and price advantages over the non-certified farmers. This has in turn led to higher net revenue from coffee for certified farmers. In Nicaragua, coffee farmers from Fairtrade and double (Fairtrade-Organic) certified cooperatives also benefit in terms of net revenue but there is no statistically significant effect on yield and household income. A comparison of the Fairtrade minimum floor price and the weight-equivalent Fairtrade cooperative price in the three countries shows that Nicaraguan Fairtrade certified farmers have obtained a higher average price than the Fairtrade mandated minimum price, whereas in Ethiopia the certified farmers received a much lower price. In India, the certified average price was closer to the minimum floor price. We conclude that coffee cooperatives and the motivation and capability of their staff play a central role in training their member farmers about each aspect of coffee growing and certification.